Hubungan Antara Kecerdasan Emosi dengan Agresivitas pada Atlet Futsal - Faris Zaky Rinanda; Haryanta Haryanta (Faculty of Psychology, Universitas Gadjah Mada, 2017)
One of the factors that contribute to the athlete’s performance is his emotional state. Athletes who are emotionally unstable tend to be more easily expressed aggression in front of opponents. This research aims to investigate the relationship between emotional intelligence and aggressiveness among futsal athlete. It was hypothesized that there a negative relationship between emotional intelligence and aggressiveness. There were 111 futsal athletes of University X from many faculties in this research. Data analysis using Product Moment correlation technique from Pearson showed rxy=-0.488 with p<0,01 pointing out that there is a significant negative correlation between emotional intelligence and aggressiveness among futsal athlete. That result proved that the hypothesis was accepted.